Nilai Perjuangan dalam Novel Arus Balik Karya Pramoedya Ananta Toer - Sabjan Badio; Burhan Nurgiyantoro; Hartono Hartono (Indonesian Language Education and Literature, 2019)
This study aims to describe the struggle of the character in the novel Arus Balik. The method used is the content analysis method. Data is obtained by reading and recording techniques. Data were analyzed with qualitative descriptive analysis techniques through data comparison, categorization, data presentation, and inference. The results showed that the struggle of the character in the Arus Balik novel by Pramoedya Ananta Toer consisted of heroism (28%), nationalism (33%), never giving up (25%), kinship (9%), and selflessness (5%). The value of the struggle for heroism consists of being wary of the enemy, defending the people, defending the truth, selflessness, daring to die, being responsible, and commanding authority. The value of nationalism consists of love for the flag itself, loyal to the leader, thinking about the safety of the country, supporting the struggle to defend the country, and participating in defending the country. The value of the unyielding struggle consists of fighting to the death and believing in your abilities. Meanwhile, the value of selfless struggle consists in overcoming not expecting respect and not expecting office.Penelitian ini bertujuan mendeskripsikan perjuangan tokoh dalam novel Arus Balik dengan metode analisis isi. Data diperoleh dengan teknik membaca dan mencatat. Data dianalisis dengan teknik analisis deskriptif kualitatif melalui perbandingan antardata, kategorisasi, penyajian data, dan inferensi. Hasil penelitian menunjukkan perjuangan tokoh dalam novel Arus Balik karya Pramoedya Ananta Toer terdiri atas heroisme (28%), nasionalisme (33%), pantang menyerah (25%), kekeluargaan (9%), dan tanpa pamrih (5%). Nilai perjuangan heroisme terdiri atas waspada terhadap musuh, membela rakyat, membela kebenaran, tidak mementingkan diri sendiri, berani mati, bertanggung jawab, serta berwibawa memimpin pasukan. Nilai nasionalisme terdiri atas cinta pada bendera sendiri, setia pada pemimpin, memikirkan keselamatan negara, mendukung perjuangan bela negara, serta ikut serta membela negara. Nilai perjuangan pantang menyerah terdiri atas melawan sampai mati dan percaya kepada kemampuan sendiri. Sementara itu, nilai perjuangan tanpa pamrih terdiri atas tidak mengharapkan penghormatan dan tidak mengharapkan jabatan.